The uses (and non-usage) of the Balanced Scorecard: a case study - Carla Ribeiro (2017)
This paper addresses an apparent empirical puzzle from a large Portuguese utility. Preliminary evidence suggested that the BSC implemented across all the business units of this organization two years before was not being used consistently, or even not used at all, by their managers; overall, actual use across the organization seemed not to be aligned with the BSC designers objectives. In line with this preliminary evidence, we confirmed that the types and the intensity of BSC use indeed varied across the business units. The most popular uses were monitoring, control and management support, while strategy communication was the least popular although it was the most emphasized objective when the BSC was proposed. Applying an extended version of Madsen and Stenheims (2014) framework of problems with BSC usage, we explain this diversity of types and intensity in BSC usage, based on multiple conceptual, technical, social and political issues. These explanatory issues include: the BSC conceptualization, alignment with new strategic priorities and timeliness; existent competing tools; organizational culture; the level of scrutiny; the not-invented-here phenomenon; the controllability principle; top management commitment; uncertainty about the BSC continuity; and power games. Through this in-depth explanation, we contribute to the literature on the diversified usages, and the non-usage, of the BSC by managers in firms which have officially adopted this tool.